The impact of inflection on word vectors - Lévai Dániel; Kornai András; Magyar Számítógépes Nyelvészeti Konferencia (15.) (2019) (Szeged) (2019)
We present a method to evaluate the similarity of word vector clusters, and use it to determine the coherence (self-similarity) and relatedness of morphologically defined clusters.